Role and plasticity of Th1 and Th17 responses in immunity to Staphylococcus aureus. Issue 12 (2nd December 2019) - Ferraro, Alessandra; Buonocore, Sofia M.; Auquier, Philippe; Nicolas, Isabelle; Wallemacq, Hugues; Boutriau, Dominique; van der Most, Robbert G.
ABSTRACT: The human commensal Staphylococcus aureus (SA) is a leading cause of skin/soft tissue and surgical-site infections, and bacteremia. Functional antibodies and T-cell-mediated immunity, particularly Th1/Th17 responses, are thought to mediate protection. Vaccine development may be hindered by modulation of vaccine-induced T cells by pathogen-activated immunoregulatory responses, e.g., via IL-10. We screened SA proteins for CD4 + T-cell-activating and IL-10/IL-17-inducing capacities using healthy donor-derived PBMCs. Responses were characterized (Th1/Th17/Th22/immunosuppressive IL-10-producing cells) using intracellular cytokine staining and flow cytometry. Phenotypic plasticity of Th1/Th17 cells was evaluated under pro- or anti-inflammatory conditions using modulatory cytokines. The impact of vaccination on SA-specific memory responses was assessed using samples from a clinical trial evaluating AS03-adjuvanted and non-adjuvanted multicomponent (CPS5/CPS8/α-toxin/ClfA) vaccines (NCT01160172). The donors exhibited SA-specific memory T-cell responses, indicative of pre-existing immunity to SA. We identified effective activators of Th1 responses (EbhA/IsaA/SdrE/MntC/Aaa/α-toxin), and Th17 and Th1/Th17 responses (EbhA/IsaA/SdrE and, to a lesser extent, α-toxin), but not of Th22 responses or IL-10 production. MRPII, IsdA, and ClfA were inefficient CD4 + T-cell activators in our assays. IL-10, likely produced by innate immune cells, influenced mainly Th1 cells by suppressing IFN-γ production. The memory CD4 + T-cells observed after long-term stimulation with α-toxin and ClfA indicated that vaccination with these proteins had induced expansion of pre-existing Th1 but not Th17 responses, without apparent adjuvant effect, confirming the trial data. The Th1/Th17-driving proteins (EbhA/IsaA/SdrE) shared low IL-10-promoting abilities and restricted phenotypic plasticity under pro- and anti-inflammatory conditions. Given the complex immunopathology and multiple virulence factors, identification of Th1/Th17-driving antigens, adjuvants and administration routes, and delineation of the role of memory responses, may advance vaccine development.